Extraversion as a moderator for resilience factors among gay men. Issue 2 (3rd April 2017) - Tse, Joseph; Kwon, Paul
ABSTRACT: The present study examined the moderating role of extraversion on the relationship between depressive symptoms and the resilience factors of social support and emotional openness (the ability to accept and process one's emotion) among gay men. Extraversion, social support, and emotional openness were all associated with lower depressive symptoms. Extraversion did not moderate the relationship between social support and depressive symptoms among gay men. Extraversion moderated the relationship between emotional openness and depressive symptoms, such that emotional openness was associated with fewer depressive symptoms, particularly among gay men with a lower level of extraversion. Clinical implications are discussed.